2015
DOI: 10.1002/app.42562
|View full text |Cite
|
Sign up to set email alerts
|

Controlled‐release drug carriers based hierarchical silica microtubes templated from cellulose acetate nanofibers

Abstract: We report a facile method to synthesize hollow silica microtubes (SMTs) from electrospun cellulose acetate fiber precursors. Specific surface areas of up to 765 m 2 /g (Brunauer-Emmett-Teller) were measured for the SMTs, which had a typical wall thickness of 100 nm and submicron inner diameters. An average pore size of 4.6 nm and pore volume of 0.41 cm 3 /g were derived from Barrett-Joyner-Halenda fitting, whereas Horvath-Kawazoe pore size distribution analysis revealed microporous median pore size and maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The FT-IR spectrum of the unmodified biogenic silica particles presented characteristic peaks at 1650 and 800 cm −1 , which are related to different vibration modes of the hydroxyl bonds in silica. The peaks at 1100 and 460 cm −1 correspond to the asymmetric stretching and bending vibration of Si-O-Si group, respectively 36 . The region at ca .…”
Section: Resultsmentioning
confidence: 99%
“…The FT-IR spectrum of the unmodified biogenic silica particles presented characteristic peaks at 1650 and 800 cm −1 , which are related to different vibration modes of the hydroxyl bonds in silica. The peaks at 1100 and 460 cm −1 correspond to the asymmetric stretching and bending vibration of Si-O-Si group, respectively 36 . The region at ca .…”
Section: Resultsmentioning
confidence: 99%
“…The similarity of the thermal behavior of cross-linked NBE and the NBE bonded to silica confirms that the BTCA cross-link is most favorable between NBE molecules than silica sites; however, the lower yield chemical reactions between NBE and silica promoted significant and important changes in the thermal behavior of the SiO2-graft-NBE system. Similarly to this study, Jia et al (2015) found different patterns in the thermal decomposition of acetylsalicylic acid after loading in amine functionalized silica microtubes, probably due the chemical bonding formed between amino group of modified silica and carboxyl groups of acetylsalicylic acid.…”
Section: Samplementioning
confidence: 44%
“…The peak at 1100 cm −1 assigned to the antisymmetric stretching vibration of Si-O-Si. Positions of 804 and 463 cm −1 were assigned to the symmetric stretching vibration and the bending vibration of Si-O, respectively, meanwhile, the peak at 954 cm −1 corresponding to the bending vibration of Si-OH [ 16 , 40 ]. After calcination, the FTIR spectra of MSNTs only shows the characteristic peak of silica, the peaks at amides Ⅰ and amide Ⅱ of SF templates and the peak of Si–OH all disappeared, indicating that the SF templates were removed and the Si-O-Si was formed between the Si-OH by removing the water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wang et al prepared TiO 2 /silica nanotubes, with a high specific area and high photocatalytic activity, by combining electrospinning technique, sol–gel process and the calcinations [ 15 ]. Jia et al prepared hierarchical MSNTs by sol-gel process with the aid of the surfactant (cetyl trimethyl ammonium bromide (CTAB)) using electrospun cellulose acetate fibers as sacrifice templates [ 16 ]. Guo et al explored the use of electrospun gelatin nanofibers as templates to produce MSNTs and evaluated their drug-loading properties [ 17 ].…”
Section: Introductionmentioning
confidence: 99%